Eastern bodies in western cockpits: An anthropometric study in the Oman military aviation. Issue 1 (31st December 2016) - Al Wardi, Yousuf M.; Jeevarathinam, Sasirajan; Al Sabei, Saleh H.
Abstract: Anthropometric selection standards of aviators in the Royal Air Force of Oman (RAFO) were assimilated from the selection standards utilized by western defence forces and aircraft manufacturers. Gradual Omanization of RAFO aircrew has led to the placement of eastern bodies in western cockpits and hence high recruit rejection rates due to incompatible anthropometric standards. This study was carried out to gain some evidence-based data on this domain. The anthropometric data of 2, 296 Omani recruits from 2003 to 2012 were collected and statistical analysis was performed to analyze the distribution of anthropometrically fit and unfit candidates. 86% ( n  = 1, 968) fulfilled the RAFO anthropometric fitness standards for aircrew duties and the remaining 14% ( n  = 328) were unfit due to non-compliance in one or many of the anthropometric parameters. 7% ( n  = 158) of the candidates had standing height below 165 cm and 3/4th ( n  = 112) of these candidates were unfit in one or many of the other RAFO anthropometric parameters. This study has provided a platform to understand the discrepancies involved in selection of eastern bodies for western cockpits. This also adds impetus to the concept of periodical updating of military recruitment standards to aid the development of the ideal man-machine interface. This approach will take into account national policy, the significant trends in body sizes of the general population and the procured aircraft profile of the country.